2023
DOI: 10.3390/ani13111843
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of Creole Cattle in the Andean Highlands Using Bio-Morphometric Measures and Zoometric Indices

Rolando Rojas-Espinoza,
Rassiel Macedo,
Alex Suaña
et al.

Abstract: Several Creole cattle biotypes can be found in the Andean highlands, and most of them are considered as being in risk of extinction. The main aim of the present study was to perform a phenotypic characterization of the Creole cattle in the Andean highlands using bio-morphometric measures and zoometric indices. Individuals from three different biotypes (Black ‘Negro’ (n = 57), Colour-Sided ‘Callejón’ (n = 20), and Brindle ‘Atigrado’ (n = 18)) from an experimental research center located in the Peruvian highland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…As the anamorphosis index decreases, the animal is considered tall of its legs and with a lower body weight [22]. In our study, the anamorphosis index found (2.53%) corresponds to a longer animal and was located within the same range of values obtained in other Ibero-American creole bovine: the Limonero creole bovine from Venezuela (2.5%) [24], the Saavedra creole bovine (2.7%) [43], the Mixtec creole bovine (2.1%) [25], the creole bovine from the province of Azuay, Ecuador (2.2%) [45], the creole bovine from the Andean highlands, Peru (2.01%) [44], the Casanare creole bovine (2.03%) [42], and the creole bovine from the Province of Huamanga (1.86%) [37]. Therefore, the Sanmartinero creole bovines phenotypically tend to be more milk producers than meat producers, with an anamorphosis index similar to the Limonero creole bovine of Venezuela.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…As the anamorphosis index decreases, the animal is considered tall of its legs and with a lower body weight [22]. In our study, the anamorphosis index found (2.53%) corresponds to a longer animal and was located within the same range of values obtained in other Ibero-American creole bovine: the Limonero creole bovine from Venezuela (2.5%) [24], the Saavedra creole bovine (2.7%) [43], the Mixtec creole bovine (2.1%) [25], the creole bovine from the province of Azuay, Ecuador (2.2%) [45], the creole bovine from the Andean highlands, Peru (2.01%) [44], the Casanare creole bovine (2.03%) [42], and the creole bovine from the Province of Huamanga (1.86%) [37]. Therefore, the Sanmartinero creole bovines phenotypically tend to be more milk producers than meat producers, with an anamorphosis index similar to the Limonero creole bovine of Venezuela.…”
Section: Discussionsupporting
confidence: 72%
“…Thus, the Sanmartinero creole bovine seems to be in a position of dual aptitude, as mentioned above. The corporal index was higher than that reported for the Limonero creole bovine from Venezuela (74.3%) [24], the Mixtec creole bovine from Oaxaca (79.9%) [25], the creole bovine Guaymi of Panama (80.52%) [40], the Barroso-Salmeco creole of Guatemala (83.55%) [41], the Casanare creole bovine from Colombia (82.5%) [42], the Saavedra creole bovine from Bolivia (82%) [43], and the creole bovine from the Andean highlands of Peru (82.98%) [44]. However, the corporal index was lower than that reported in Ecuador for the creole bovine from the Province of Azuay (86.8%) [45], the creole bovine from the Province of Huamanga (88.97%) [37], the creole bovine of the Ecuadorian coast (87.5) [46], the creole bovine from Uruguay (88.2%) [47], the creole bovine from the Province of Santa Elena, Ecuador (95.03%) [48], and the creole bovine from the Province of Loja (115.9%) [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to taurine breeds from temperate zones, Criollo cattle are renowned for high fertility and excellent reproductive performance under tropical conditions [21,29,100,101] and using the CSS method we detected several genes associated with these traits. For example, in the Blanco Orejinegro breed a BTA7 CSS cluster region contains the CATSPER3 gene exclusively expressed in the testis, which encodes a sperm-specific ion channel protein directly linked to sperm motility and male fertility in many species, including cattle [102].…”
Section: Genomic Signatures Of Selection For Fertility and Reproducti...mentioning
confidence: 99%